Glaucomatous, glaucoma-like, and non-glaucomatous optic neuropathy in high myopia: the two-continent study - Jonas, Jost B.; Bikbov, Mukharram M.; Kazakbaeva, Gyulli M.; Wang, Ya Xing; Nangia, Vinay; Milea, Dan; Lamirel, Cédric; Jonas, Rahul A.; Panda-Jonas, Songhomitra (Investigative ophthalmology & visual science, 2025)
The purpose of this study was to examine prevalences of glaucomatous (GON), glaucoma-like (GLON), and non-glaucomatous optic neuropathy (NGON) in highly myopic individuals. The population-based investigations of the Ural Eye and Medical Study (UEMS; n = 5899 participants; aged = 40+ years), Ural Very Old Study (UVOS; n = 684 participants; aged = 85+ years), Ural Children Eye Study (UCES; n = 4933 participants; aged = 11.8 ± 3.2 years), Central India Eye and Medical Study (CIEMS; n = 4711 participants, aged = 30+ years), and Beijing Eye Study (BES; n = 4439 participants, aged = 40+ years) were conducted in Bashkortostan/Russia, Nagpur/India, and Beijing/China, respectively. Prevalences of NGON and GLON/GON in the UEMS (n = 116 highly myopic individuals), UVOS (n = 13), UCES (n = 101), CIEMS (n = 47), and BES (n = 149 eyes) were 34 of 116 (29.3%, 95% confidence interval [CI] = 21.0-38.0) and 10 of 116 (8.6%, 95% CI = 3.1-14.1), 4 of 13 (31%, 95% CI = 2-60), and 4 of 13 (31%, 95% CI = 2-60), 0 of 101 and 0 of 101, and 16 of 47 (34.0%, 95% CI = 20.0-48.1) and 14 of 47 (29.8%, 95% CI = 16-43), and 34 of 149 (22.8%, 95% CI = 16-30) and 20 of 149 (13.4%, 95% CI = 8-19), respectively. In all cohorts, higher NGON prevalence and degree were associated (most P < 0.01) with longer axial length and wider myopic parapapillary beta/gamma zone. Higher GLON/GON prevalence and degree were associated (most P < 0.01) with larger optic disc size and, less significantly, with longer axial length. The proportion of eyes with elevated IOP or anti-glaucomatous therapy was 3 of 10 (30%), 1 of 4 (25%), 0 of 14 (0%), and 1 of 20 (5%), respectively. Highly myopic eyes had considerable prevalences of NGON and GLON/GON, usually higher than 20% and 10%, respectively. The single IOP reading was ≤21 millimeters of mercury (mm Hg) in ≥70% of the eyes with GLON/GON. NGON (associated with large parapapillary myopic beta/gamma zone) and GLON/GON (associated with large optic disc size) differed in their relationships. Prevalences of both optic neuropathies increased in a nonlinear manner with longer axial length, reaching values of 50% to 100% in extreme high myopia.